Multi-year observations of near-bed hydrodynamics and suspended sediment at the core of the estuarine turbidity maximum of the Changjiang Estuary - Z. Zhou; J. Ge; J. Ge; D. S. van Maren; D. S. van Maren; D. S. van Maren; H. Luan; H. Luan; W. Guo; J. Ma; Y. Tao; P. Xu; et al. (Earth System Science Data)
A comprehensive multi-year field campaign, the North Passage Channel Measurements (NP-ChaM), was designed and executed to enhance our understanding of the hydrodynamics and sediment dynamics in the North Passage, the primary navigation channel of the Changjiang Estuary, China. The NP-ChaM campaign comprised eight observational sites and spanned 50 d, distributed over 4 years, including two dry seasons and two wet seasons. A series of tripod systems, equipped with multiple instruments, were deployed on the seabed to monitor near-bed physical processes reliably.